Pakistan : political roots and development, 1947-1999 - Safdar Mahmood (Karachi : Oxford University Press, 2000)
"The focus of the book is on Pakistan's political history. With a chapter on the establishment of Pakistan as a backgrounder, the book thoroughly examines constitution-making and the characteristic features of various constitutions and why and how these did not work effectively. It analyses the working of the military governments of Ayub Khan, Yahya Khan, and Ziaul Haq as well as the working of the elected civil governments after Pakistan's return to civilian rule in 1985. It also analyses the programmes and functioning of various political parties along with their election performance and leadership." "The book offers a concise analytical statement on the major aspects of Pakistan's history, constitution-making, political parties and the democratic process and foreign policy. No other single volume covers such a long period of history, examining a variety of subjects and issues."--BOOK JACKET.
Includes bibliographical references (p. [421]-427) and index.
A copy was presented to the Library of Congress on the occassion of its Bicentennial by the Embassy of Pakistan.
Keywords: Pakistan movement; Pakistan -- Politics and government; Pakistan -- Politics and government -- 1971-